Exploring the development of cross-cultural social connectedness: A qualitative study of Malaysian international students in China - Lu, Lu; Sun, Tong (Journal of International Students, 2025)
Social interaction is essential for international students in rebuilding support systems in their host country; however, the complexity of this process remains insufficiently explored. Guided by the conceptual framework of social connectedness, this qualitative case study examines the types, influencing factors, and characteristics of social interactions among four Malaysian international students at a Chinese higher-education institution. Analysis of data from face-to-face interviews, informal conversations, and social media posts revealed five social connectedness types—expansion, deepening, weakening, avoidance, and flexibility—shaped by distinct personal and contextual factors. Further analysis revealed three characteristics of social connectedness: proactive, nongoal-oriented, and restricted. This study extends the conceptual framework by demonstrating the adaptive functions of disconnection, interpersonal tensions within deep relationships, and the context-dependent nature of social interaction flexibility. The study also advances the understanding of how agency shapes diverse trajectories of social connectedness, supporting cross-cultural learning and personal growth.